Column stability during welding - Vild, Martin; Bajer, Miroslav; Barnat, Jan (IOP Publishing Ltd., 2019)
This research is part of the project of strengthening of steel members under load using plates welded parallel to the member axis. Buckling load resistance of columns has to be checked during welding under compressive load. A part of a cross-section is ineffective due to high temperature near the weld. The centre of gravity is shifted and the decisive cross-section is loaded by additional bending moment. Moreover, the weld causes deformations which are higher than in case of regular welding. This paper presents authors’ method determining the buckling load resistance of the compressed member during welding. The method takes into account the column cross-section, slenderness, and effective intensity of the welding heat source. The column is treated as a stepped member and its Euler’s critical load is decreased. The deformation of the column and the stress are determined with regards to second order effects. The method is validated by experiments performed in the laboratory of Department of Metal and Timber Structures at Brno University of Technology in November 2017. Columns with cross-sections HEA 100 and SHS 100×5 with the length of 3 m were loaded by the maximal force determined using the analytical method and under this constant load the weld bead was being laid from the bottom of the column to 15 cm above the mid-height. Then, still during welding, the force was gradually increased until the column failed via flexural buckling. Measured values of load resistance, deformations and temperatures are compared with the authors’ analytical method. All six specimens resisted the maximum calculated load and failed at slightly higher loads.

This research is part of the project of strengthening of steel members under load using plates welded parallel to the member axis. Buckling load resistance of columns has to be checked during welding under compressive load. A part of a cross-section is ineffective due to high temperature near the weld. The centre of gravity is shifted and the decisive cross-section is loaded by additional bending moment. Moreover, the weld causes deformations which are higher than in case of regular welding. This paper presents authors’ method determining the buckling load resistance of the compressed member during welding. The method takes into account the column cross-section, slenderness, and effective intensity of the welding heat source. The column is treated as a stepped member and its Euler’s critical load is decreased. The deformation of the column and the stress are determined with regards to second order effects. The method is validated by experiments performed in the laboratory of Department of Metal and Timber Structures at Brno University of Technology in November 2017. Columns with cross-sections HEA 100 and SHS 100×5 with the length of 3 m were loaded by the maximal force determined using the analytical method and under this constant load the weld bead was being laid from the bottom of the column to 15 cm above the mid-height. Then, still during welding, the force was gradually increased until the column failed via flexural buckling. Measured values of load resistance, deformations and temperatures are compared with the authors’ analytical method. All six specimens resisted the maximum calculated load and failed at slightly higher loads.
Column stability during welding
Keywords: Steel; column; buckling; welding; Steel; column; buckling; welding